Evaluation of a short instrument for measuring health-related quality of life in oncological patients in routine care (HELP-6): an observational study - Schrage, Theresa; Görlach, Mirja; Betz, Christian Stephan; Bokemeyer, Carsten; Kröger, Nicolaus; Mueller, Volkmar; Krüll, Andreas; Schulz, Holger; Bleich, Christiane (Frontiers in Psychology, 2023)
Purpose Patient-reported outcomes have not been sufficiently implemented into the routine care of cancer patients because the existing instruments are often too long and complex or not cancer-specific. The aim of this study is the determination of psychometric properties and item reduction of a newly developed health-related quality of life (HrQoL) questionnaire for use in oncological clinical routines. Methods This observational study with a repeated measurements design included oncological inpatients and outpatients. A total of 630 patients participated at the first point of measurement and 404 at the second point of measurement. To evaluate the instrument, we conducted hierarchical confirmative factor analyses and for further validation correlated the resulting factors with standardized and validated HrQoL measurements. Test–retest reliability and responsiveness to change were tested. Results The developed questionnaire “HELP-6” (“Hamburg Inventory for Measuring Quality of Life in Oncological Patients”) has a six-factor structure and has moderate-to-good convergent validity (r= −0.25 –−0.68). Test–retest reliability was moderate-to-good (r =0.56−0.81, p < 0.001). Indications for responsiveness to change were found for three dimensions. The final version of the questionnaire HELP-6 has six dimensions with one item each. Conclusion With the HELP-6 instrument for measuring HrQoL in cancer patients, we provide a short and practical patient-reported outcome instrument. Though responsiveness to change could not be confirmed for all dimensions in this study, the HELP-6 includes time-efficient completion and evaluation and is informative in relevant HrQoL dimensions of cancer patients. Therefore, the HELP-6 poses an important addition to inpatient and outpatient routine cancer care. Trial registration This study was registered at Open Science Framework (https://osf.io/y7xce/), on 9 June 2018.